The Effectiveness of Artificial Intelligence Usage as Translation Medium among English Literature Student of UIN Sunan Gunung Djati Bandung - Mukti, Muhammad Abdee Praja; Maulana, Muhamad Trian; Rohmah, Kharisma Nur; Abqoriyyah, Fourus Huznatul; Saehu, Andang (Journal of English Education Forum (JEEF), 2024)
The integration of Artificial Intelligence (AI) in translation services has transformed the landscape of linguistic studies. This study assesses the effectiveness of AI-driven translation tools among English Literature students at UIN Sunan Gunung Djati Bandung, focusing on translation accuracy, usability, and impact on language learning. Using a mixed-methods approach, the research collected quantitative data through questionnaires and supported it with a literature review. Findings indicate that 96.6% of students regularly use AI translation tools, with a majority finding them helpful. However, concerns about over-reliance on these tools and their potential negative impact on language skill development were noted. The study highlights the dual role of AI tools in enhancing learning while requiring human oversight for accuracy and contextual relevance. Recommendations for improving AI tools include ensuring contextually accurate translations, enhancing vocabulary databases, and integrating human input. Overall, while AI translation tools significantly aid students' academic activities, a balanced approach is crucial to avoid dependency and ensure the development of independent language skills